Homozygous mutation in NUP107 leads to microcephaly with steroid-resistant nephrotic condition similar to Galloway-Mowat syndrome. Issue 6 (9th March 2017) - Rosti, Rasim Ozgur; Sotak, Bethany N; Bielas, Stephanie L; Bhat, Gifty; Silhavy, Jennifer L; Aslanger, Ayca Dilruba; Altunoglu, Umut; Bilge, Ilmay; Tasdemir, Mehmet; Yzaguirrem, Amanda D; Musaev, Damir; Infante, Sofia; et al.
Abstract : Background: Microcephaly with nephrotic syndrome is a rare co-occurrence, constituting the Galloway-Mowat syndrome (GAMOS), caused by mutations in WDR73 (OMIM: 616144). However, not all patients harbour demonstrable WDR73 deleterious variants, suggesting that there are other yet unidentified factors contributing to GAMOS aetiology. Methods: Autozygosity mapping and candidate analysis was used to identify deleterious variants in consanguineous families. Analysis of patient fibroblasts was used to study splicing and alterations in cellular function. Results: In two consanguineous families with five affected individuals from Turkey with a GAMOS-like presentation, we identified a shared homozygous variant leading to partial exon 4 skipping in nucleoporin, 107-KD ( NUP107 ). The founder mutation was associated with concomitant reduction in NUP107 protein and in the obligate binding partner NUP133 protein, as well as density of nuclear pores in patient cells. Conclusion: Recently, NUP107 was suggested as a candidate in a family with nephrotic syndrome and developmental delay. Other NUP107 -reported cases had isolated renal phenotypes. With the addition of these individuals, we implicate an allele-specific critical role for NUP107 in the regulation of brain growth and a GAMOS-like presentation.